PEREMPUAN DAN KARIER: PERBANDINGAN KESENJANGAN UPAH GENDER DI INDONESIA DENGAN NEGARA-NEGARA DI EROPA (STUDI KASUS: FINLANDIA, INGGRIS, PRANCIS, DAN JERMAN) - Hartika Arbiyanti (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2020)
In some countries, women's wages lag behind men. The most recent study shows that most of the payments made by gender in wage growth are issued during the first ten years of workers in the labor market. Some part of the contribution of growth can be explained by investment in human capital and work mobility between men and women. In Europe, gender payments occur in several countries. This research will discuss the factors of gender payment in the UK, Finland, Germany, and France - which incidentally relates to gender payments by comparing other countries - with qualitative research methods.